Born under the Bad Sign: Intergenerational Effects of the Finnish Great Depression of the Early 1990s - Eiji Mangyo; Mika Haapanen; Petri Böckerman (Institute of Labor Economics (IZA), 2024)
This paper investigates the effect of a major economic recession on the educational attainment of the next generation. Our analysis is based on nationwide longitudinal registry data on Finland. We focus on the heterogenous effects of the recession on households of different socioeconomic statuses. We find that the effects of the early 1990s recession on the educational attainment of the next generation were more severe for children with nontertiary-educated parents than those with tertiary-educated parents, implying that the recession aggravated the pattern of societal inequality in Finland. Importantly, the deterioration of the home environment was the primary mechanism through which the recession adversely affected the educational attainment of the next generation.
Keywords: I24; J12; O15; 330; early-life events; parental socioeconomic status; intergenerational effects; education; family dissolution; Finland